Removal heavy metals from industrial wastewater using activated carbon from coconut coir - Emmery, Dayang Dirk (2019)
Heavy metals are metallic chemical elements. It has a high density and toxic towards the ecosystem and human's life. The sources of heavy metals are from mining activities, agricultural activities, lead-acid batteries, chemical waste, sewage and pharmaceutical industries. Reverse osmosis, chemical precipitation, chemical oxidant, and air stripping are the conventional treatment to treat the wastewater. Nowadays, those methods are costly and difficult to conduct. Adsorption process is one of the method that can be used. This is because adsorption process is easier and cheaper than those methods. There are many types of agricultural waste like coconut coir that can be used as the adsorbent to remove the heavy metals from industrial wastewater. Coconut coir has been chosen for this study to achieve the objectives. The aim of this study is to determine the characteristic of the industrial wastewater, to obtain the optimum dosage of the activated carbon from coconut coir and to determine the effect of pH with constant contact time in removing the heavy metals for cadmium and lead. Atomic Adsorption Spectrophotometer (AAS) has been conducted for the analysis of heavy metals. The coconut coir were obtained from the coconut industrial, washed and dried under the sunlight. Then, the coconut coir was soaked in 5% hydrogen chloride (HCI) solution for one night. Next, the coconut coir was dried under the sunlight again. After dried, the coconut coir was ready to dry in the furnace for 20 minutes with 550 °C. Later, the activated carbon from coconut coir was tested for the optimum dosage and effect of pH and contact time. The dosages of activated carbon have been used are I 000 mg, 3000 mg and 5000 mg while for pH are 2, 6 and 9. The contact time for all tests were two hours with sample of I L.Test of Atomic Adsorption Spectrophotometer (AAS) is conducted for analysis of heavy metals. As the treatment conducted, the concentration of cadmium was reducing for two hours period where I 000 mg removed 60 % of cadmium 3000 mg removed 55% of cadmium and 5000 mg removed 58 % of cadmium while the concentration of lead also reducing where 1000 mg removed 52 % of lead 3000 mg removed 56 % of lead and 5000 mg removed 57 % of lead. The effective of pH and constant time for cadmium is at pH of 6 while lead is at pH of 2. As the treatment continued, the heavy metals of cadmium and lead can be reduce from time to time of contact time that able to remove the harmful materials from the industrial wastewater.